Costs and decision-making in state entities (2017)
This paper aims to show a reference framework of the cost system in the public sector in Colombia towards the strengthening of the National System of Public Accounting -SNCP - aimed at the recognition and calculation of costs. It is therefore necessary to establish whether public entities currently have a cost culture oriented towards administrative decision making that allows information to be clearly identified in terms of the cost and impact that is being generated with each service or offered And that finally can guarantee the good management and the appropriate destination of the resources of the State.